Are Nondenominational Colleges More Liberal Than Denominational Colleges?: A Comparison of Faculty Religious Identity, Beliefs, Attitudes, and Actions. Issue 3 (27th May 2019) - Glanzer, Perry L.; Cockle, Theodore F.; Graber, Britney; Jeong, Elijah; Robinson, Jessica A.
Abstract: Throughout American history, scholars called Christian higher education by other names. They used terms such as "denominational, " "sectarian, " "church-related, " "church-sponsored, " "church-based, " and "church-affiliated" higher education to describe Christian higher education. What these terms failed to include, however, were the increasing number of nondenominational institutions that began to emerge in the nineteenth century. In The Dying of the Light, James Burtchaell (1998 ) did include these institutions in his argument. He suggested that nondenominational colleges and universities had the same weakness as denominational institutions that abandoned their church connections. In fact, compared to institutions that kept their church ties, in Burtchaell's eyes, they appeared to be weaker institutions since they lacked direct denominational support. Apart from Burtchaell's one historical case study, very little empirical literature exists that supports this argument. This study explores this claim empirically, and compares faculty attitudes, theological beliefs, and religious behaviors at denominational and nondenominational institutions that are part of the Council for Christian Colleges & Universities (CCCU). Respondents included 1, 999 full-time faculty from 49 CCCU institutions. Contrary to what certain scholars claim, results demonstrated that faculty at nondenominational institutions did not significantly differ in their theological beliefs from their denominational counterparts. Further empirical research is needed to understand the reasons for this outcome, although we offer some possible hypotheses.